Sustainable Practices of Environmental Management in the Preservation of Archives in Public Libraries in Rivers State (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This study investigated sustainable practices of environmental management in the preservation of archives in public libraries in Rivers state. Two objectives and its corresponding research questions and hypotheses guided this study. The descriptive survey design was adopted for this study. The population of interest in this study was 514 library staff from the Rivers state library board and staff from the Jubilee library in Port Harcourt. The sample size of this study was 399 library staff, of which 227 were from the board of the Rivers state library and 172 were from the Port Harcourt branch of the Jubilee library. The sample size was calculated by Taro Yamane's formula, and a two-stage sampling method was employed to select the sample size. Stratified and simple random sampling were used in the process. A self-structured instrument titled sustainable practices of environmental management in the preservation of records questionnaire was employed for data collection. Face and content validation was ensured by three experts. The instrument yielded reliability coefficients of 0.81 with the use of Cronbach Alpha reliability method. Mean and Standard Deviation were used in answering research questions while z-test was used for the inferential statistics. The findings revealed that Sustainable practices for environmental management in public libraries in Rivers state include using acid-free folders, having large sculptures shielded from elements, and having the archives environment protected from flooding. Microforms are not used to shield delicate unpublished documents and artworks are not stored in enclosures made of acrylic plexiglass. It was concluded and recommended that archivists in the libraries should e supported by the government to employ sustainable practices such as microforms, acrylic plexiglass, ultraviolet filtering windows and low-velocity vacuum systems to protect both unpublished and published materials from degradation.